Consolidation Chemotherapy Provided Survival Benefit for Esophageal Squamous Cell Carcinoma Patients Who Underwent Concurrent Chemoradiotherapy Lower Than 60 Gy - Hualei Zhang; Qi Wang; Ping Wang; Bo Tang (Thoracic Cancer)
ABSTRACT Background The efficacy of consolidation chemotherapy (CCT) following concurrent chemoradiotherapy (CCRT) has not been clearly defined in esophageal squamous cell carcinoma (ESCC). This study determined which patients with stage II‐IVA ESCC benefitted from CCT. Methods 351 patients with ESCC were retrospectively reviewed. 185 patients received CCRT alone and 166 received CCRT plus CCT. Subset analyses were conducted on all patients' characteristics. Factors associated with survival were analyzed using the Kaplan–Meier method and a Cox proportional hazards model. The Propensity score matching (PSM) technique was used to compensate for differences in patients' characteristics. Results The median OS were 17.7 months and 38.4 months in the CCRT alone group and CCRT+CCT group (p = 0.002), respectively. Multivariable Cox regression analysis determined that CCT was associated with improved OS (p = 0.002, HR 0.592, 95% CI 0.423–0.829); After PSM, relative to the CCRT group, patients who received CCT experienced improved OS (17.7 months vs. 38.4 months, p = 0.0139). Subgroup analysis showed that CCT was more effective in radiation dose < 60 Gy (p = 0.002, HR 0.368, 95% CI 0.194–0.700). After matching between radiation dose, in the low dose cohort, the median OS was 13.2 months and 20.7 months in the CCRT alone group and CCRT+CCT group, respectively (p = 0.0028), the multivariate analysis results showed that CCT retained its statistical significance (p = 0.002, HR 0.353, 95% CI 0.183–0.681). In the high dose cohort, the median OS were 21.6 months and 23.6 months in the CCRT alone group and CCRT+CCT group, respectively (p = 0.5512). Conclusions We recommend that CCT treatment should be considered for ESCC patients who underwent CCRT using < 60 Gy. Further studies are needed to confirm these results.